Changes in muscle activity during double poling with increasing speeds in elite cross-country skiers - Rapp, W.; Stöggl, T.; Müller, E.; Holmberg, H. C.; Lindinger, S. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Double poling (DP) in cross country (XC) skiing is an increasingly important technique especially for sprint skiing. Earlier DP studies have mainly focused on kinematics and kinetics (Hoffman et al. 1995; Millet et al. 1998; Nilsson et al. 2004) but only few have investigated EMG activity (e.g. Holmberg et al. 2005). Little is known about neuromuscular control patterns during DP, which may also have an important positive effect on athletic performance. In running and jumping studies, it could be shown that Stretch shortening cycle contraction (SSC) enhances motor performance (Gollhofer et al. 1992, Komi 2000, Kyröläinen et al. 2005). Therefore, the goal of this study was to evaluate neuromuscular activation patterns during DP across increasing speeds.